Resiliensi dan Sabar sebagai Respon Pertahanan Psikologis dalam Menghadapi Post-Traumatic - Umi Rohmah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2012)
Earthquake, accidents, the closure of the factory layoffs, rape, divorce, the death of the loved ones, poverty, suffering from a disease are many events which can be caused stress and frustration. Such incidents often cause trauma in individuals who do not have a strong psychological defenses. And if the trauma is not addressed properly will lead to post-traumatic disorder. A variety of unpleasant events raises a variety of different reactions. Some emotions burst out. There is also the emotion exploding inside. Some people describe themselves as victims. There are also some people who pass their distress by pointing to a new life and overcome a challenge. This paper tried to describe how resilience ability and sabar (patience) as a defense mechanism to face this psychological problems.